Deletion of Atf6α impairs astroglial activation and enhances neuronal death following brain ischemia in mice. (6th January 2015) - Yoshikawa, Akifumi; Kamide, Tomoya; Hashida, Koji; Ta, Hieu Minh; Inahata, Yuki; Takarada‐Iemata, Mika; Hattori, Tsuyoshi; Mori, Kazutoshi; Takahashi, Ryosuke; Matsuyama, Tomohiro; Hayashi, Yutaka; Kitao, Yasuko; et al.
Abstract To dissect the role of endoplasmic reticulum (ER) stress and unfolded protein response in brain ischemia, we investigated the relevance of activating transcription factor 6α (ATF6α), a master transcriptional factor in the unfolded protein response, after permanent middle cerebral artery occlusion (MCAO) in mice. Enhanced expression of glucose‐regulated protein78, a downstream molecular chaperone of ATF6α, was observed in both neurons and glia in the peri‐infarct region of wild‐type mice after MCAO. Analysis using wild‐type and Atf6α−/− mice revealed a larger infarct volume and increased cell death in the peri‐ischemic region of Atf6α−/− mice 5 days after MCAO. These phenotypes in Atf6α−/− mice were associated with reduced levels of astroglial activation/glial scar formation, and a spread of tissue damage into the non‐infarct area. Further analysis in mice and cultured astrocytes revealed that signal transducer and activator of transcription 3 (STAT3)‐glial fibrillary acidic protein signaling were diminished in Atf6α−/− astrocytes. A chemical chaperone, 4‐phenylbutyrate, restored STAT3‐glial fibrillary acidic protein signaling, while ER stressors, such as tunicamycin and thapsigargin, almost completely abolished signaling in cultured astrocytes. Furthermore, ER stress‐induced deactivation of STAT3 was mediated, at least in part, by the ER stress‐responsive tyrosine phosphatase, TC‐PTP/PTPN2. These results suggest that ER stress plays critical roles in determining the level of astroglial activation and neuronal survival after brain ischemia.<boxed-text content-type="graphic" id="jnc12981-blkfxd-1001" position="anchor" orientation="portrait"> </boxed-text> We here suggest a mechanism triggered after brain ischemia in which the enhanced level of endoplasmic reticulum (ER) stress—caused by deletion of the activating transcription factor ATF6α—leads to suppression of the STAT3‐GFAP signaling, inhibition of astroglial activation/glial scar formation, and enhanced level of neuronal death in the peri‐ischemic area. This is mediated, at least in part, through the ER stress‐responsive tyrosine phosphatase, TC‐PTP. CNTF, ciliary neurotrophic factor; GFAP, Glial fibrillary acidic protein; IL‐6, interleukin 6; LIF, leukemia inhibitory factor; STAT3, signal transducer, and activator of transcription 3.